2019
DOI: 10.1289/ehp4601
|View full text |Cite
|
Sign up to set email alerts
|

Time-Varying Exposure to Air Pollution and Outcomes of in Vitro Fertilization among Couples from a Fertility Clinic

Abstract: Background:A few studies suggest that air pollution may decrease fertility, but prospective studies and examinations of windows of susceptibility remain unclear.Objective:We aimed to examine the association between time-varying exposure to nitrogen dioxide (NO2), ozone (normalO3), fine particulate matter <2.5μm (PM2.5), and black carbon (BC) on in vitro fertilization (IVF) outcomes.Methods:We included 345 women (522 IVF cycles) for the NO2, normalO3, and PM2.5 analyses and 339 women (512 IVF cycles) for the BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Patients then underwent controlled ovarian hyperstimulation by luteal-phase gonadotropin-releasing hormone (GnRH) agonist, GnRH antagonist downregulation, or GnRH agonist flare protocol, with follicular synchronization and pituitary downregulation as clinically indicated and previously described [17,[19][20][21]. During treatment with recombinant gonadotropins (follitropin beta, Follistim, Merck, Kenilworth, NJ, or follitropin alpha, Gonal-F, EMD-Serono; and m e n o t r o p i n s , M e n o p u r o r R e p r o n e x , F e r r i n g Pharmaceuticals, Parsippany, NJ), patients were serially monitored with transvaginal ultrasound and serum estradiol (E 2 ) to assess follicular measurements and endometrial thickness.…”
Section: Ovarian Stimulation Protocolsmentioning
confidence: 99%
“…Patients then underwent controlled ovarian hyperstimulation by luteal-phase gonadotropin-releasing hormone (GnRH) agonist, GnRH antagonist downregulation, or GnRH agonist flare protocol, with follicular synchronization and pituitary downregulation as clinically indicated and previously described [17,[19][20][21]. During treatment with recombinant gonadotropins (follitropin beta, Follistim, Merck, Kenilworth, NJ, or follitropin alpha, Gonal-F, EMD-Serono; and m e n o t r o p i n s , M e n o p u r o r R e p r o n e x , F e r r i n g Pharmaceuticals, Parsippany, NJ), patients were serially monitored with transvaginal ultrasound and serum estradiol (E 2 ) to assess follicular measurements and endometrial thickness.…”
Section: Ovarian Stimulation Protocolsmentioning
confidence: 99%
“…NO 2 and PM 2.5 are associated with increased ART cycle failure rates. 13 Carbon monoxide 14 and PM 2.5 15 are associated with decreased conception rates. Decreased live birth rates are associated with NO 2 , 12,15,16 SO 2 , 17 ozone, 15 and PM 2.5 .…”
Section: Environmental Factors In Maternal Health Subfertility Pregnancy Complications and Maternal Morbiditymentioning
confidence: 99%
“…Decreased live birth rates are associated with NO 2 , 12,15,16 SO 2 , 17 ozone, 15 and PM 2.5 . 13 An ecologic association between air pollutant peaks and monthly in vitro fertilization pregnancy failure rates has been observed. 11…”
Section: Environmental Factors In Maternal Health Subfertility Pregnancy Complications and Maternal Morbiditymentioning
confidence: 99%
“…Since 1978, more than five million children were born through assisted reproductive technology (ART) treatment ( 15 ). This provides the opportunity for a novel evaluation of the effects of air pollutants because it is possible to observe many early reproductive outcomes, such as embryo implantation that can't be observed in natural pregnancy ( 16 ). Furthermore, the timing of conception is known with certainty because key events in the IVF treatment are timed and trigger by a physician, exact exposure periods of air pollutants can be determined ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…This provides the opportunity for a novel evaluation of the effects of air pollutants because it is possible to observe many early reproductive outcomes, such as embryo implantation that can't be observed in natural pregnancy ( 16 ). Furthermore, the timing of conception is known with certainty because key events in the IVF treatment are timed and trigger by a physician, exact exposure periods of air pollutants can be determined ( 16 , 17 ). To date, several studies have reported the association between air pollutants exposure and follicle growth, a reduced rate of implantation, pregnancy or live birth in women who underwent ART treatment, but the results were inconsistent ( 16 , 18 21 ).…”
Section: Introductionmentioning
confidence: 99%